Newborn Care Education on Mother's Readiness to Care for Babies Independently - Wahyuni Wahyuni; Irmasanti Fajrin (Sarana Ilmu Indonesia (salnesia), 2023)
Preparation for newborn care (BBL) is important throughout the duration of pregnancy, particularly in the third trimester of gestation. Handling BBL that is not good can be fatal because it will cause abnormalities that cause lifelong disability to death. The purpose of this research was to identify the effect of Newborn Baby Care Education on Mothers' Readiness to Independently Care for their babies at BPM Sifra Langowan. The research design was quasi-experimental with a control group pre-post test design that involved 20 subjectss in the experimental group and 20 subjectss in the control group using the purposive sampling technique. The research results showed that the mean readiness to care for newborn babies before the intervention in the experimental group was 2,85, and after the intervention was 1.30, with a mean difference of 1,15 and a P value of 0,000 (p-value<0,05). In the control group, the mean readiness to care for newborn babies before the intervention was 3,00, and after the intervention was 2,80, with a mean difference of 0,20 and a p-value of 0,042 (p-value<0,05). It could be concluded that there was an influence of having provided newborn baby care education on mothers' readiness to independently care for their babies.